Fabrication of polyamide thin-film nanocomposite membranes with enhanced surface charge for nitrate ion removal from water resources. Issue 6 (19th March 2017) - Ghaee, A.; Zerafat, M. M.; Askari, P.; Sabbaghi, S.; Sadatnia, B.
ABSTRACT: Exclusion due to membrane surface charge is considered as one of the main separation mechanisms occurring in charged membranes, which can be varied through various approaches to affect membrane rejection performance. In this study, thin-film composite (TFC) polyamide (PA) membranes were fabricated via interfacial polymerization of m -phenylenediamine ( m - PDA) and 2, 4- diaminobenzene sulfonic acid with trimesoyl chloride (TMC) on a polysulfone sub-layer. The ability of the prepared membrane to remove nitrate ions from water resources has been investigated. In order to improve membrane permeability, zeolite- PA thin film nanocomposite (TFN) membranes were fabricated by incorporating natural zeolite nanoparticles obtained through ball milling of an Iranian natural zeolite powder in the interfacial polymerization process. The size, morphology and specific surface area of the as-obtained nanozeolite were characterized using particle size analysis, FE-SEM and BET. The functional groups, morphology and surface charge of the membrane were characterized using ATR- FTIR, SEM and zeta potential analyses. Also, field- emission scanning electron microscopy (FE- SEM) and energy dispersive X- ray spectroscopy (EDS) were used to determine the distribution of nanozeolite in TFN membranes. The influence of zeolite addition to surface roughness was accessed by atomic force microscopy. The performance of TFC and TFN membranes was evaluated in terms of pure water flux and nitrate rejection. The results showed that in case of sulfonated diamine, nitrate ions rejection was enhanced from 63% to 85% which could be attributed to surface charge enhancement. TFN permeability was almost doubled by the addition of nanozeolite.